If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8(x + 3) = 3x + 9 + 7x Reorder the terms: 8(3 + x) = 3x + 9 + 7x (3 * 8 + x * 8) = 3x + 9 + 7x (24 + 8x) = 3x + 9 + 7x Reorder the terms: 24 + 8x = 9 + 3x + 7x Combine like terms: 3x + 7x = 10x 24 + 8x = 9 + 10x Solving 24 + 8x = 9 + 10x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-10x' to each side of the equation. 24 + 8x + -10x = 9 + 10x + -10x Combine like terms: 8x + -10x = -2x 24 + -2x = 9 + 10x + -10x Combine like terms: 10x + -10x = 0 24 + -2x = 9 + 0 24 + -2x = 9 Add '-24' to each side of the equation. 24 + -24 + -2x = 9 + -24 Combine like terms: 24 + -24 = 0 0 + -2x = 9 + -24 -2x = 9 + -24 Combine like terms: 9 + -24 = -15 -2x = -15 Divide each side by '-2'. x = 7.5 Simplifying x = 7.5
| -1y+6y=-6 | | x^2-21x-10=0 | | 1+35=3+5x | | 2x^2y^2+24xy+1=0 | | -8x+-9x=-4 | | 1-y=x | | 5x+6=x^2 | | -7x=-84 | | 2t^4+15t^2-125=0 | | 5n+25=50 | | -5=-5(x+4)-2x | | 2x^2+2y^2+8x+30y+40=0 | | 7x+30=x^2 | | -7x+13=-99 | | t+4.13=12.39 | | 3t*3t*3t*3t*3t= | | -7+91x-84x^2=0 | | 2q+5=-3 | | X+40=66 | | 5(2r-3)=15 | | 7y-2y=20 | | 7.17y=-56.17 | | -64=-8p | | 4(x-9)=6(x+7) | | -3x-6x=-9 | | t^3-2t^2-7t+2=0 | | 5h+h-4h+1-2h=b | | M-30=-110 | | w=1/2*4 | | 7x+-4=# | | -2=-2-2k | | 47.0362-39.7204= |